2015
DOI: 10.1128/aac.00029-15
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Extended-Spectrum-β-Lactamase- and NDM-1-Producing Enterobacteriaceae among Pregnant Women in the Community in a Low-Income Country: a Potential Reservoir for Transmission of Multiresistant Enterobacteriaceae to Neonates

Abstract: The spread of extended-spectrum-␤-lactamase-producing Enterobacteriaceae (ESBL-PE) in low-income countries, where the burden of neonatal sepsis is high, may have a serious impact on neonatal mortality rates. Given the potential for mother-to-child transmission of multiresistant bacteria, this study investigated the ESBL-PE rectal colonization among pregnant women at delivery in the community in Madagascar and estimated a prevalence of 18.5% (95% confidence interval, 14.5% to 22.6%). One strain of Klebsiella pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 20 publications
3
62
2
Order By: Relevance
“…. Other studies in different countries have reported lower rates of ESBL-E carriage in pregnant women compared to this study, for example 2.9% (26 out of 901) in Norway in 2012 (13), 8.6% (18 out of 209) in Germany in 2012-2013 (14), 31.7% (32 out of 101) in Nigeria in 2014 (33), and 18.6% (66 out of 356) in Madagascar in 2014(21). The high prevalence of ESBL-E carriage in pregnant women in this study is probably associated with the high prevalence of ESBL-E carriage in communities in Indonesia(8)(9)(10).…”
contrasting
confidence: 49%
“…. Other studies in different countries have reported lower rates of ESBL-E carriage in pregnant women compared to this study, for example 2.9% (26 out of 901) in Norway in 2012 (13), 8.6% (18 out of 209) in Germany in 2012-2013 (14), 31.7% (32 out of 101) in Nigeria in 2014 (33), and 18.6% (66 out of 356) in Madagascar in 2014(21). The high prevalence of ESBL-E carriage in pregnant women in this study is probably associated with the high prevalence of ESBL-E carriage in communities in Indonesia(8)(9)(10).…”
contrasting
confidence: 49%
“…Several studies have identified the 3GCRB-colonized mother as substantial risk factor for colonization of the neonate [4,6,9,10,24,25]. Recent data of the German surveillance system for nosocomial infection in preterm infants on neonatal wards (NEO-KISS) indicate that 8.45 % of neonatal colonizations with multidrug-resistant gram-negative bacteria were brought in by colonized mothers [21].…”
Section: Discussionmentioning
confidence: 99%
“…Bebell et al (2017)) identified single marital status (OR 2.6, 95% CI 1.1-6.1, p = 0.026), low CD4+ count of <200/ml (OR 2.9, 95% CI 1.1-7.7, p = 0.031), and current UTI symptoms (OR 2.5, 95% CI 1.1-6.0, p = 0.03) as independent predictors of ESBL-E infection. The following elements were not found to be significantly associated with ESBL-E colonization/infection in these three studies: being employed or being a housewife (Tito et al 2017), drinking water supply from a spring or a well (Chereau et al, 2015), and hospitalization in the last 3 months (Djuikoue et al 2016a,b).…”
Section: Factors Associated With Esbl-e In Pregnant Women In Africamentioning
confidence: 94%